Gamifying of English Learning with Educandy at MTs. Muhammadiyah 13 Solokuro Lamongan - Arifatin, Fais Wahidatul; Mafruudloh, Naajihah; Masruroh, Masruroh (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study explores the potential of gamification through Educandy in enhancing English language learning outcomes among junior high school students at MTs. Muhammadiyah 13. Employing a Research and Development (R&D) framework using the ADDIE model, this study integrates both quantitative and qualitative analyses to measure effectiveness. Findings reveal a significant increase in student motivation and vocabulary retention, positioning Educandy as a viable tool for technology-integrated education. This study conducted at MTs. Muhammadiyah 13, Solokuro, Lamongan. The research subjects comprised seventh and eight-grade students during the 2024/2025 academic year, there are 40 respondents in these classes. The results indicate that the gamified learning media received high validation scores from experts, confirming its feasibility for classroom use. This study concludes that gamification using Educandy effectively improves English learning outcomes and motivation, especially for having vocabularies improvement. However, challenges such as limited access to technology and the need for teacher training must be addressed to ensure broader implementation. Future research should explore the long-term impact of gamification on learning retention and its application to other English skills, such as speaking and listening.